Karakter Genetik Populasi Bedeng 61B Desa Wonokarto Kabupaten Lampung Timur Pasca Program Kolonisasi Pemerintah Belanda - Yustin Nur Khoiriyah (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2014)
Gene and genotype frequencies are important in a population characterizing. Based on the frequency of these gene and genotype, distinctiveness of population can be determined (Arisuryanti et al., 2007). Gene frequencies of population can be changed if there are evolutionary forces (the factors that play a role in changing the allele and genotype frequencies), such as, mutation, migration, non-random mating, genetic drift and natural selection (Arisuryanti & Daryono, 2007). Migration and genetic drift were thought to be a factor that changed alleles and genotype frequencies in the population of Lampung. Witrianto (2010) showed migration programs that were triggered by the Dutch government, it was called colonization. Therefore, in the population of Lampung, indication of changes in allele and genotype frequencies were need to be evaluated. The results showed that frequency of alleles IA, IB and IO in the population were 0.17; 0.21 and 0.62, respectively. Frequency of genotype IAIA, IAIO, IBIB, IBIO, IAIB and IOIO were 0.290; 0.2108; 0.0441; 0.2604; 0.0650 and 0.3800, respectively. Chi Square test showed that the value of X2 were 0,07 (X2 < α critical value at 5% for dF = 3). It can be concluded that alleles and genotype distribution of ABO blood system in the population were in accordance with Hardy Weinberg equilibrium law, so that the equilibrium legal status were applied in this population. Genetic drift and gene flow were not affected alleles and genotype changes. The process of microevolution were not occur in the population of people from the 61 B plot of Wonokarto village.Keywords: character of genetic population, post-colonization of Dutch government, the 61 B plot ofWonokarto village